The Norm of a Closed Technology and the Straight-Down-the-Turnpike Theorem - Winter, S. G. (Review of Economic Studies, 1967)
Journal Article The Norm of a Closed Technology and the Straight-Down-the-Turnpike Theorem Get access S. G. Winter, Jr. S. G. Winter, Jr. The Rand Corporation, Santa Monica, California Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 34, Issue 1, January 1967, Pages 67–84, https://doi.org/10.2307/2296571 Published: 01 January 1967